Utilizing Robotics in Health Care: Increasing the Efficiency and Accuracy of Patient Therapy - Mehdi Karimi; Sahar Yazdani (Yayasan Adra Karima Hubbi, 2025)
The healthcare industry has increasingly embraced technological innovations to improve patient care and streamline medical procedures. Among these advancements, robotics has emerged as a powerful tool in enhancing the efficiency and accuracy of patient therapy. Robotics in healthcare can perform tasks such as surgery, rehabilitation, and patient monitoring with precision, leading to better outcomes and reduced human error. This study explores the integration of robotics in healthcare, focusing on its impact on patient therapy, including rehabilitation and therapeutic assistance. Using a mixed-methods approach, this research evaluates both qualitative and quantitative data from healthcare facilities implementing robotic technologies. The findings show that robotic systems have led to a 30% improvement in rehabilitation outcomes, 20% reduction in therapy time, and significant enhancement in treatment accuracy. These results highlight the potential of robotics to not only increase the efficiency of therapy but also provide more personalized and consistent care. The study concludes that the widespread adoption of robotics in healthcare can significantly improve patient therapy and overall healthcare delivery. However, challenges such as cost, integration with existing healthcare systems, and training requirements must be addressed. Future research should focus